Remote Left Ventricular Hemodynamic Monitoring Using a Novel Intracardiac Sensor. (May 2018) - Mondritzki, Thomas; Boehme, Philip; White, Jason; Park, Jin Woo; Hoffmann, Jessica; Vogel, Julia; Kolkhof, Peter; Walsh, Stuart; Sandner, Peter; Bischoff, Erwin; Dinh, Wilfried; Hüser, Jörg; et al.
Abstract : Background—: Heart failure (HF) remains the most common reason for hospital admission in patients aged >65 years. Despite modern drug therapy, mortality and readmission rates for patients hospitalized with HF remain high. This necessitates further research to identify early patients at risk for readmission to limit hospitalization by timely adjustment of medical therapy. Implantable devices can monitor left ventricular (LV) hemodynamics and remotely and continuously detect the early signs of decompensation to trigger interventions and reduce the risk of hospitalization for HF. Here, we report the first preclinical study validating a new batteryless and easy to implant LV-microelectromechanical system to assess LV performance. Methods and Results—: A miniaturized implantable wireless pressure sensor was adapted for implantation in the LV apex. The LV-microelectromechanical system sensor was tested in a canine model of HF. The wireless pressure sensor measurements were compared with invasive left heart catheter-derived measurements at several time points. During different pharmacological challenge studies with dobutamine or vasopressin, the device was equally sensitive compared with invasive standard procedures. No adverse events or any observable reaction related to the implantation and application of the device for a period of 35 days was observed. Conclusions—: Our miniaturized wireless pressure sensor placed in the LV (LV-microelectromechanical system) has the potential to become a new telemetric tool to earlier identify patients at risk for HF decompensation and to guide the treatment of patients with HF. Abstract : Supplemental Digital Content is available in the text.